MENDIDIK ANAK MENJADI SHALIH DAN SHALIHAH DALAM ISLAM - Nanang Zakaria (CV. ADIBA AISHA AMIRA, 2023)
Education in the family is the first and most important environment in shaping children's character. Therefore, in the process of educating a child, both parents should have knowledge and insight about the best way to educate children, especially how to educate according to Islamic teachings, because forming a generation of righteous and righteous Muslims cannot be separated from the two main Islamic foundations. al-Quran and al-Hadith. Moving on from that, the focus of the journal issue is centered on educating children in the perspective of Islamic teachings so that they can create a generation of Muslims who are rahmatan lil alamin. Exposure in this study was analyzed qualitatively through the results of library research (library research). And the results of the study concluded that: (1) the concept of children's education in Islamic teachings is an educational concept that originates from the Qur'an and Hadith which is capable of producing generations of righteous and righteous Muslims, both individually and socially; (2) Children's education in Islamic teachings consists of several stages that must be carried out by educators or parents. To determine its success, parents/educators are required to educate children according to the development and differences in the characters they are doing; and (3) Children's education in Islam is the best method for preparing and forming the moral, spiritual, and social ethos aspects of children. This is due to the personality of Rasulullah SAW who is the best example in all respects; both in terms of worship, words and deeds.